The mitochondrion-like organelle of Trimastix pyriformis contains the complete glycine cleavage system - Zubáčová, Zuzana; Novák, Lukáš; Bublíková, Jitka; Vacek, Vojtěch; Fousek, Jan; Rídl, Jakub; Tachezy, Jan; Doležal, Pavel; Vlček, Cestmír; Hampl, Vladimír (PloS one, 2013)
All eukaryotic organisms contain mitochondria or organelles that evolved from the same endosymbiotic event like classical mitochondria. Organisms inhabiting low oxygen environments often contain mitochondrial derivates known as hydrogenosomes, mitosomes or neutrally as mitochondrion-like organelles. The detailed investigation has shown unexpected evolutionary plasticity in the biochemistry and protein composition of these organelles in various protists. We investigated the mitochondrion-like organelle in Trimastix pyriformis, a free-living member of one of the three lineages of anaerobic group Metamonada. Using 454 sequencing we have obtained 7 037 contigs from its transcriptome and on the basis of sequence homology and presence of N-terminal extensions we have selected contigs coding for proteins that putatively function in the organelle. Together with the results of a previous transcriptome survey, the list now consists of 23 proteins - mostly enzymes involved in amino acid metabolism, transporters and maturases of proteins and transporters of metabolites. We have no evidence of the production of ATP in the mitochondrion-like organelle of Trimastix but we have obtained experimental evidence for the presence of enzymes of the glycine cleavage system (GCS), which is part of amino acid metabolism. Using homologous antibody we have shown that H-protein of GCS localizes into vesicles in the cell of Trimastix. When overexpressed in yeast, H- and P-protein of GCS and cpn60 were transported into mitochondrion. In case of H-protein we have demonstrated that the first 16 amino acids are necessary for this transport. Glycine cleavage system is at the moment the only experimentally localized pathway in the mitochondrial derivate of Trimastix pyriformis.
Keywords: exprese genu; Gene Expression; Mitochondria; Saccharomyces cerevisiae; H-protein systému glycinového štěpení; Eukaryota; transferasy; mitochondriální proteiny; Multienzyme Complexes; organely; Carrier Proteins; Glycine Decarboxylase Complex H-Protein; Mitochondrial Proteins; Organelles; multienzymové komplexy; Transferases; Amino Acid Oxidoreductases; oxidoreduktasy aminokyselin; transportní proteiny; mitochondrie